Pengaruh Kualitas Layanan, Kemudahan Penggunaan, dan Promosi terhadap Kepuasan Konsumen Pengguna Gojek - Fransiska, Fransiska; Aquinia, Ajeng (Jurnal Manajemen Bisnis dan Keuangan, 2023)
Many companies are utilizing the advancement of the internet effectively and efficiently to be able to compete competitively with their competitors. Transportation is one of the service sectors that has changed due to the development of internet technology. The population in this study are consumers who use Gojek in the city of Semarang and the sample taken is 100 respondents. The sampling technique used is a purposive sampling technique. This study uses multiple linear regression analysis with the help of SPSS application data. The purpose of this study was to analyze the effect of service quality, ease of use, and promotion on consumer satisfaction with Gojek users. The results of this study indicate that service quality, ease of use, and promotion have a positive and significant effect on customer satisfaction.